Multibeam bathymetry raw data (Kongsberg EM712 entire dataset) of RV HEINCKE during cruise HE628 - Evgenia A Bazhenova; Peter Betlem; Nil Rodes; Miriam Römer (PANGAEA, 2025)
Raw bathymetry data were collected using the ship extquotesingles own Kongsberg EM 712 multibeam echosounder during the RV Heincke cruise HE628 FJORDGAS. The cruise took place between 2023-09-04 and 2023-10-01 (Longyearbyen, Svalbard - Stavanger, Norway). The expedition focused on mapping seafloor gas discharge in the western fjords of Svalbard, where bathymetric surveys took place between 2023-09-04 and 2023-09-24. Transit data were collected between 2023-09-24 and 2023-09-30 and are of less quality due to the bad weather conditions on the way to Stavanger. Data are unprocessed and therefore contain incorrect depth measurements (artifacts). Sound velocity profiles (SVP) were regularly collected in all the working areas and are integrated into the raw files. Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).